2019
DOI: 10.1002/rrq.244
|View full text |Cite
|
Sign up to set email alerts
|

Literacy and Phonological Skills in Oral Deaf Children and Hearing Children With a History of Dyslexia

Abstract: Oral deaf children and hearing children with dyslexia both experience literacy challenges, although their reasons differ. The authors explored the problems underlying poor literacy in each group and drew implications for reading interventions. Data were collected using standardized literacy and phonological measures from 69 severe‐to‐profoundly prelingually deaf children ages 10 and 11 years, all communicating with spoken language, and compared with equivalent data from 20 hearing children with a history of dy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 117 publications
(225 reference statements)
1
18
0
Order By: Relevance
“…It is worth highlighting that, in the current sample of deaf children, phonological awareness was strongly related to single-word reading ability (r = .61 for onset matching with YARC Single-Word Reading subtest). This supports numerous previous studies that have reported a correlation between phonological awareness and reading development in deaf children (Campbell & Wright, 1988;Dyer et al, 2003;Harris & Beech, 1998;Herman et al, 2019). Factors such as the age of the children tested and the measures used are likely to influence the strength of this relationship, and these factors may explain the inconsistencies between previous studies (see Mayberry et al, 2011).…”
Section: Discussionsupporting
confidence: 84%
“…It is worth highlighting that, in the current sample of deaf children, phonological awareness was strongly related to single-word reading ability (r = .61 for onset matching with YARC Single-Word Reading subtest). This supports numerous previous studies that have reported a correlation between phonological awareness and reading development in deaf children (Campbell & Wright, 1988;Dyer et al, 2003;Harris & Beech, 1998;Herman et al, 2019). Factors such as the age of the children tested and the measures used are likely to influence the strength of this relationship, and these factors may explain the inconsistencies between previous studies (see Mayberry et al, 2011).…”
Section: Discussionsupporting
confidence: 84%
“…The authors found striking similarities in spelling, word reading and non-word reading in both DHH children and children with dyslexia, and in line with earlier studies, the DHH-children showed poor phonological awareness. The children with dyslexia had a larger vocabulary than the DHH-children, and vocabulary was shown to be a strong predictor for good literacy outcomes for the group of deaf children, but not for the group with children with dyslexia (Herman et al, 2019).…”
Section: Introductionmentioning
confidence: 87%
“…Many prior studies identifying vocabulary as a strong predictor of reading achievement in deaf children have focused on expressive vocabulary (e.g., Easterbrooks and Huston 2008;Kyle and Harris 2006;Kyle et al 2016;Herman et al 2019). Measuring expressive vocabulary allows researchers to deal with the variability in language background typically found in deaf children.…”
Section: Vocabularymentioning
confidence: 99%